Epidemiology of coronary artery bypass grafting at the Hospital Beneficência Portuguesa, São Paulo - Sousa,Alexandre Gonçalves de (2015)
Introduction: The knowledge of the prevalence of risk factors and comorbidities, as well as the evolution and complications in patients undergoing coronary artery bypass graft allows comparison between institutions and evidence of changes in the profile of patients and postoperative evolution over time. Objective: To profile (risk factors and comorbidities) and clinical outcome (complications) in patients undergoing coronary artery bypass graft in a national institution of great surgical volume. Methods: A retrospective cohort study of patients undergoing coronary artery bypass graft in the hospital Beneficência Portuguesa de São Paulo, from July 2009 to July 2010. Results: We included 3,010 patients, mean age of 62.2 years and 69.9% male. 83.8% of patients were hypertensive, 36.6% diabetic, 44.5% had dyslipidemia, 15.3% were smokers, 65.7% were overweight/obese, 29.3% had a family history of coronary heart disease. The expected mortality calculated by logistic EuroSCORE was 2.7%. The isolated CABG occurred in 89.3% and 11.9% surgery was performed without cardiopulmonary bypass. The most common complication was cardiac arrhythmia (18.7%), especially acute atrial fibrillation (14.3%). Pneumonia occurred in 6.2% of patients, acute renal failure in 4.4%, mediastinites in 2.1%, stroke in 1.8% and AMI in 1.2%. The in-hospital mortality was 5.4% and in isolated coronary artery bypass graft was 3.5%. The average hospital stay was 11 days with a median of eight days (3-244 days). Conclusion: The profile of patients undergoing coronary artery bypass graft surgery in this study is similar to other published studies.